The Puffin Book of Modern Children's Verse - Brian Patten (Editor) (UK Puffin Books, 2006)
The Puffin Book of Modern Children's Verse is the definitive collection of modern children's poetry of our time. Enchanting, funny, exciting and poignant, there is every kind of poem for every kind mood. Discover the very best of children's poetry from the greats of the poetry world including, Allan Ahlberg, W. H. Auden, Charles Causley, Roald Dahl, T. S. Eliot, Thomas Hardy, Ted Hughes, Rudyard Kipling, Philip Larkin, Laurie Lee, Roger McGough, Spike Milligan, A. A. Milne, Wilfred Owen, Brian Patten, Sylvia Plath, Michael Rosen, Ian Serrallier, W.B. Yeats, Benjamin Zephaniah and many, many more!